Produção Textual e leitura no contexto escolar - Fiorese, Eliane (Linguagens & Cidadania, 2017)
Education must happen with responsibility, because it requires from educator a constant dedication and improvement. We know the school environment may propitiate the development of efficient practices, which aims interaction of the person with the society, which it lives. In this article they settled down considerations on the reading and production text, aiming to establish the importance to these relations and to address a new one to look front to the educational process for the current day.